ANNUAL ACUTE HOSPITAL COST OF PAEDIATRIC HEAD INJURY IN AUSTRALIA – A PAEDIATRIC RESEARCH IN EMERGENCY DEPARTMENTS INTERNATIONAL COLLABORATIVE (PREDICT) STUDY. Issue 12 (18th November 2016) - Cheek, JA; Lyttle, M; Oakley, E; Babl, F; Borland, M; Dalziel, K; Kanal, GN; Phillips, N; Gilhotra, Y; Kochar, A; Dalton, S; McCaskill, M; et al.
Abstract : Objectives & Background: Children with head injuries (HIs) frequently present to acute care settings. Most injuries are mild, but a small portion of patients have clinically significant intracranial injuries. An attempt to estimate the cost of paediatric HIs using prospectively collected data has never been attempted in Australia. We aimed to estimate the total cost paediatric HI in Australia and provide an understanding of the costs associated with different causative and presentation factors. Methods: The study was embedded in a prospective observational study of 20, 255 children <18 years designed to validate three published clinical decision rules. Each patient's hospital presentation was micro-costed and then extrapolated to an annualised Australia-wide figure using Australian Independent Hospital Pricing Authority data. Results: There were 109, 729 cases of HI in children aged 0–18 years across Australia in the fiscal year 2012–2013 (1.67% of total emergency presentations). The average cost of each HI was $1348.21 [95%CI: 1173.02 to 1523.40]. The total cost of HI in Australia was $147.94 million [95% CI: 128.71 to 167.17]. Regression and generalized linear models both demonstrate that motor vehicle accidents (MVAs) and non-accidental injury (NAI) are the most significant drivers of cost, as are injuries presenting with vomiting, seizure and loss of consciousness greater than 5 minutes. Conclusion: Paediatric head injury represents a significant cost to the Australian healthcare system. Efforts to reduce the main drivers of cost–MVAs and NAI – may reduce this.